Potential toxic elements in surface water of Mokosh Beel, Gazipur, Bangladesh: Ecological and human health risk assessment for recreational users - Md. Shahriar Mahmud; M. Safiur Rahman; S.A. Dina; M. Rifat Nasher; Tasrina R. Choudhury; Bilkis A. Begum; Abdus Samad (Heliyon)
Mokosh Beel, a significant wetland in Bangladesh, is increasingly impacted by industrial effluents, leading to potential ecological and human health risks. This study evaluates the surface water quality of Mokosh Beel by analyzing both physicochemical parameters (pH, DO, EC, TDS, and salinity) and the concentrations of potential toxic elements (PTEs) (i.e., Mn, Cu, Ni, Pb, As, Cd, Co, Cr, Sb, and Zn). The findings reveal that most water quality parameters, except pH, exceeded local and international guidelines, indicating poor water quality. Among the PTEs, Mn (269.13 μg/L), Cr (33.20 μg/L), and Pb (71.47 μg/L) surpassed recommended safety limits. The spatial distribution analysis identified Mn and Pb as the primary pollutants based on the single-factor pollution index. The Nemerow pollution index indicated mild to moderate pollution, while the heavy metal pollution index (HPI) and heavy metal evaluation index (HEI) suggested a low degree of pollution at most sampling sites. Principal component analysis (PCA) and hierarchical cluster analysis (HCA) linked the majority of PTEs to industrial sources, particularly from tannery, leather, and paint industries. The potential ecological risk index (PERI) showed minimal ecological risk, but the hazard index (HI) indicated non-carcinogenic risks for children, although adults were not significantly affected. Carcinogenic risk assessments highlighted Pb and Cd as key contributors, with risks exceeding the critical threshold for both children and adults. This study underscores the urgency of addressing industrial pollution to safeguard both ecological health and human well-being, particularly for vulnerable populations like children. Policymakers must implement sustainable water management strategies to mitigate the ongoing contamination of Mokosh Beel.